Fundamentos del enfoque de competencias para la vida y de la transversalidad en el Ministerio de Educación Pública - Ingrid Bustos-Rojas; Viviana Richmond-González (Universidad Nacional, Costa Rica, 2007)
This article refers to the vision of the world of the people, knowledge, human development, the educational phenomena, curriculum, and the teaching-learning process from the M.E.P.'s transversality in Costa Rica. Starting with this base; it also presents the conceptualisation of the transversalty, it's topics, cross curricular topics and competences for life; as basic elements for the development of this model in the costarican Educative System.